The purpose and function of the warranty in the canonical matrimonial law - Bartczak, Adam (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
Warranty is an institution functioning in the canonical matrimonial law. In this matrimonial law warranty took a characteristic meaning. Its mission is to protect an institution of the marriage. In the article there is an analysis of warranty with respect to the purpose and function to be played in the matrimonial law. Both the purpose and the function cannot be reduced to a single issue. The variety of references makes this institution very important, especially in a view of the multi-religious society.